An overview of self-administered health literacy instruments. - Braden O Neill; Daniela Gonçalves; Ignacio Ricci-Cabello; Sue Ziebland; Jose Valderas (PLoS ONE)
With the increasing recognition of health literacy as a worldwide research priority, the development and refinement of indices to measure the construct is an important area of inquiry. Furthermore, the proliferation of online resources and research means that there is a growing need for self-administered instruments. We undertook a systematic overview to identify all published self-administered health literacy assessment indices to report their content and considerations associated with their administration. A primary aim of this study was to assist those seeking to employ a self-reported health literacy index to select one that has been developed and validated for an appropriate context, as well as with desired administration characteristics. Systematic searches were carried out in four electronic databases, and studies were included if they reported the development and/or validation of a novel health literacy assessment measure. Data were systematically extracted on key characteristics of the instruments: breadth of construct ("generic" vs. "content- or context- specific" health literacy), whether it was an original instrument or a derivative, country of origin, administration characteristics, age of target population (adult vs. pediatric), and evidence for validity. 35 articles met the inclusion criteria. There were 27 original instruments (27/35; 77.1%) and 8 derivative instruments (8/35; 22.9%). 22 indices measured "general" health literacy (22/35; 62.9%) while the remainder measured condition- or context- specific health literacy (13/35; 37.1%). Most health literacy measures were developed in the United States (22/35; 62.9%), and about half had adequate face, content, and construct validity (16/35; 45.7%). Given the number of measures available for many specific conditions and contexts, and that several have acceptable validity, our findings suggest that the research agenda should shift towards the investigation and elaboration of health literacy as a construct itself, in order for research in health literacy measurement to progress.